Editor’s Letter - Sánchez Gutiérrez, José (Mercados y Negocios, 2024)
Congratulations to the entire editorial team on joining Scopus. We are sure it is a moment of pride for everyone at Mercados y Negocios. We must keep up the excellent work and strive to be the best daily! This issue contains five research articles that have the potential to significantly contribute to their respective fields, thanks to the rigorous peer-review process they have undergone.